Building Cladding using Liner Trays: Experimental and Numerical Approach. Issue 2 (September 2019) - Georgescu, Mircea; Ungureanu, Viorel; Gruin, Aurelian; Floricel, Andra
Abstract: Liner trays are large channel-type thin-walled steel sections with two narrow flanges, two webs and one wide flange, very frequently used in practice both to resist perpendicular uniformly distributed loading from wind and create a diaphragm effect at the level of buildings cladding. Such cladding systems are normally built using a required number of horizontally laid inter-connected adjacent liner trays plus an external skin of sinusoidal or trapezoidal sheeting installed perpendicularly to their direction (with vertical corrugations). This results in a stiff metal cellular system (as outer wall of the building) having its inner space filled with thermo insulating material. When trying to evaluate the resistance of such elements by experiment, the specific constructional details play a major role and create quite complex problems in establishing a correct experimental procedure. Thus an experimental setup made of three joined liner trays is proposed with adequate detailing to match the real situation of such claddings. The investigation on liner trays was conducted by a joint team belonging to The Romanian Academy (Timisoara Branch), The Politehnica University of Timisoara (CEMSIG Laboratory) and The National Institute for Research and Development (INCD-URBAN-INCERC)–Timisoara Division. Aspects related to the experimental setup, test results (in terms of found collapse modes) experimentally and numerically determined resistances are emphasized. A comparison with code based theoretical results and FE simulation is presented and discussed in the final part.